Why context matters? Divisive normalization and canonical microcircuits in psychiatric disorders. (July 2020) - Northoff, Georg; Mushiake, Hajime
Highlights: Context-dependence of neuronal activity. Divisive normalization can account for context-dependence. Context-dependence is mediated by canonical microcircuits. Canonical microcircuits include inhibition and excitation. Inhibition and excitation are abnormal in psychiatric disorders like schizophrenia and depression. Abstract: Neural activity on cellular, regional, and behavioral levels shows context-dependence. Here we suggest the processing of input-output relationships in terms divisive normalization (DN), including (i) summing/averaging inputs and (ii) normalizing output against input stages, as a computational mechanism to underlie context-dependence. Input summation and output normalization are mediated by input-output relationships in canonical microcircuits (CM). DN/CM are altered in psychiatric disorders like schizophrenia or depression whose various symptoms can be characterized by abnormal context-dependence.